Training In Psychotherapy: A Response to Kottler - Lubbe, Trevor (PINS-Psychology in Society, 2026)
In addressing herself to a topic referred to as the ’’widespread exclusion of homosexuals from psychoanalytic training" Amanda Kottler (PINS 22, 1997) mentions the Letter of Concern (LOC) sent by a group of UK psychoanalysts and psychotherapists to prominent British journals about a forthcoming public lecture by Charles Socarides, whose views on homosexuality are well known for being controversial. In a footnote Ms Kottler finds it noteworthy to state that "people working at the Tavistock Institute are conspicuous by their absence from the list of signatories". Ms Kottler must mean the Tavistock Clinic not the Tavistock Institute - the only Tavistock Institute is an independent organisation which runs group relations conferences in the UK and Internationally, while the Tavistock Clinic is the largest national training school for psychoanalytic psychotherapy in the UK. Yet several of the signatories to the LOC clearly mention their association, either as present or past staff members, with the Tavistock Clinic -while many others are well known graduates of the Clinic. I wish this misrepresentation to be noted by your readers.